First- and second-generation black hole and neutron star mergers in 2+2 quadruples: population statistics. Issue 4 (24th July 2021) - Hamers, Adrian S; Fragione, Giacomo; Neunteufel, Patrick; Kocsis, Bence
ABSTRACT: Recent detections of gravitational waves from mergers of neutron stars (NSs) and black holes (BHs) in the low- and high-end mass gap regimes pose a puzzle to standard stellar and binary evolution theory. Mass-gap mergers may originate from successive mergers in hierarchical systems such as quadruples. Here, we consider repeated mergers of NSs and BHs in stellar 2+2 quadruple systems, in which secular evolution can accelerate the merger of one of the inner binaries. Subsequently, the merger remnant may interact with the companion binary, yielding a second-generation merger. We model the initial stellar and binary evolution of the inner binaries as isolated systems. In the case of successful compact object formation, we subsequently follow the secular dynamical evolution of the quadruple system. When a merger occurs, we take into account merger recoil, and model subsequent evolution using direct N -body integration. With different assumptions on the initial properties, we find that the majority of first-generation mergers are not much affected by secular evolution, with their observational properties mostly consistent with isolated binaries. A small subset shows imprints of secular evolution through residual eccentricity in the LIGO band, and retrograde spin-orbit orientations. Second-generation mergers are ∼10 7 times less common than first-generation mergers, and can be strongly affected by scattering (i.e. three-body interactions) induced by the first-generation merger. In particular, scattering can account for mergers within the low-end mass gap, although not the high-end mass gap. Also, in a few cases, scattering could explain highly eccentric LIGO sources and negative effective spin parameters.